Chemistry of nucleic acids - Lönnberg, Harri (Boston : De Gruyter, 2024)
Life in all its forms is based on nucleic acids which store and transfer genetic information. The book addresses main aspects of synthesis, hydrolytic stability and solution equilibria of nucleosides, nucleotides and oligonucleotides, as well as synthesis of their structural analogs that are of interest in chemotherapy. In addition, recent achievements in chemistry of catalytic nucleic acids, development of oligonucleotide based drugs and novel strategies for their targeting and delivery are discussed. The central theme always is the correlation of structure and function.
Includes references and index
Keywords: Nucleic acids; DNA; RNA; Nucleotides; Molecular biology